Investment Bank Reputation and IPO Qualifications - Li, Yubo (European Scientific Journal, ESJ, 2016)
This study examines the influence of investment bank’s reputation and political connection on the IPO qualification of Chinese firms. The results show that firms which are sponsored by prestigious investment banks are more likely to pass the regular screening process. Also, the investment bank’s political connections have no significant impact on the IPO qualification. Furthermore, we compared the various investment banks’ customer’s characteristic. Thus, the results show that the customers of prestigious investment banks have more large-scale, are high growth companies, and are more central enterprises. This indicates that high reputation investment banks tend to choose low risk and high growth prospective IPO companies in order to avoid damage to the reputation.